Upaya Pemerintah Desa dalam Menangani Pernikahan Usia Anak - Muhamad Zakie Mubarak; Rispawati Rispawati; Yuliatin Yuliatin (MANAZHIM, 2022)
The aims of this study are: 1) To find out the efforts made by the village government in handling child marriage in Saba Village, Janapria District, Central Lombok Regency. 2) To find out the factors that influence the village government's efforts in handling child marriage in Saba Village, Janapria District, Central Lombok Regency. This research uses a qualitative approach with a descriptive type of research. The subjects in this study were the village head and village staff and the informants were community leaders and the head of the hamlet. Data was collected by means of observation, documentation and interviews. The data analysis was carried out by data reduction and data presentation. The results showed that 1) there were 2 efforts made by the Saba Pemdes in dealing with child marriage, namely preventive efforts and repressive efforts. Preventive efforts include socialization related to child marriage, discussions and posyandu. Repressive efforts include receiving reports, mediating to parents, mediating to children, handling cases and advocating. 2) There are inhibiting factors for pemdes efforts including the parental factor, the drop-out factor in children's education, the low level of family economics, the customary offense factor and the free association factor. 3) There are supporting factors for pemdes efforts, including support factors from the child's parents and the education factor that the child is currently taking, which reduces the chances of child marriage.